FORMULASI DAN EVALUASI FISIK SABUN CAIR EKSTRAK DAUN SAGA (ABRUS PRECATORIUS L.) DENGAN VARIASI KOH: Formulation And Physical Evaluation Of Saga Leaf Extract Liquid Soap (Abrus Precatorius L.) With Variations KOH - Eka S, Nur Afifah; Elvaretta R.I, Louisa; Friska, Septiana; Fatmi, Ota Fiya; Sihhono, Sihhono; Aulia, Cantika (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
Soap is often combined with sodium and potassium salt formulations of fatty acids derived from vegetable oils or animal fats. This study discusses the needs of the skin such as the manufacture of liquid soap with natural ingredients saga leaves. The research method used is by maceration method with 70% ethanol solvent soaked for 3 days at room temperature stirred every 8 hours. The purpose of the research that has been done is the formulation and evaluation of liquid soap preparation from saga leaf extract (Abrus Precatorius L.). Quality testing includes organoleptic test, pH test, viscosity test and foam height Test. Organoleptic test results showed that liquid soap is yellow, rancid odor, fine texture, pH test obtained all the results exceed the requirements of SNI 8-11, viscosity test all the results obtained are too low than the requirements of SNI is 400-4000cps and high foam test results obtained also do not meet the requirements of SNI is about 13-220 mm